2021
DOI: 10.1021/acs.est.1c05686
|View full text |Cite
|
Sign up to set email alerts
|

SO2-Induced Alkali Resistance of FeVO4/TiO2 Catalysts for NOx Reduction

Abstract: Selective catalytic reduction of nitrogen oxides with ammonia (NH3-SCR) is an efficient NO x abatement strategy, but deNO x catalysts suffer from serious deactivation due to the coexistence of multiple poisoning substances such as K, SO2, etc. in the flue gas. It is essential to understand the interaction among various poisons and their effects on NO x abatement. Here, we unexpectedly identified the K migration behavior induced by SO2 over K-poisoned FeVO4/TiO2 catalysts, which led to alkali-poisoning buffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…So far, the research about improving the alkali‐resistance of FeVO 4 /TiO 2 has hardly been reported. Very recently, we just reported that the activity of K‐poisoned FeVO 4 /TiO 2 could be recovered by sulfuration treatment because of the SO 2 ‐induced K migration from active sites [10] . However, this work does not essentially supply a design strategy about improving the alkali‐resistance of the FeVO 4 /TiO 2 .…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…So far, the research about improving the alkali‐resistance of FeVO 4 /TiO 2 has hardly been reported. Very recently, we just reported that the activity of K‐poisoned FeVO 4 /TiO 2 could be recovered by sulfuration treatment because of the SO 2 ‐induced K migration from active sites [10] . However, this work does not essentially supply a design strategy about improving the alkali‐resistance of the FeVO 4 /TiO 2 .…”
Section: Introductionmentioning
confidence: 91%
“…NO x causes several pollution issues like haze, ozone, acid rain, among others [4–7] . Nowadays, selective catalytic reduction (SCR) of NO x with ammonia is generally recognized as the most efficient technology for reducing the abatement of NO x [8–10] . The commercial V 2 O 5 ‐WO 3 /TiO 2 catalysts have widespread application in coal‐fired power plants because of the satisfactory SCR activity in temperature of 300–400 °C [11,12] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The catalyst with a molar ratio of Ce/Ti = 1:1 was denoted as CeTiO x , representing the composed oxides of Ce and Ti. The K 2 O (1 wt %, the amount of alkali metal accumulated on catalysts in stream for 600–700 h) and CdO (3 wt %, the comparable amount with As in poisoned industrial SCR catalysts) ,, poisons were loaded on CeTiO x through a wet impregnation method with KNO 3 and Cd­(CH 3 COO) 2 ·2H 2 O precursors. , The alkali metal-poisoned, heavy metal-poisoned, and copoisoned samples were denoted as CeTiO x -K, CeTiO x -Cd, and CeTiO x -K & Cd, respectively. Aiming to study the poisoning resistance of the acid additive, a certain amount of H-ZSM-5 (mass ratios of 10–50 wt % among modified catalysts) was mixed with the CeTiO x catalyst to obtain the modified catalysts.…”
Section: Experimental Sectionmentioning
confidence: 99%